Plans for Villages in the Margin of the Lagoon with an Accentuation on Tourism Advancement (Case Study: Village Rogbeh, Shadegan, Iran) - Mousavi Shalheh, Seyed Mohammad; Rostami, Elham; Mousavi, Seyed Majid; Shirin Jani, Somayeh (New Countryside, 2025)
This research examines the potential for sustainable tourism development in Rogbeh Village, a socio-economically marginalized settlement situated along the ecologically fragile Shadegan Lagoon in southwestern Iran. Confronting intersecting challenges of environmental degradation (e.g., pollution, habitat loss) and socio-economic vulnerability (e.g., youth outmigration, infrastructure deficits), this study proposes a participatory tourism framework that synergistically integrates Indigenous cultural heritage—including Arabic-speaking Bahrani traditions, vernacular stilt architecture, and artisanal houri canoe craftsmanship—with regenerative infrastructure design. Employing a robust mixed methodology, the research synthesizes: comprehensive SWOT analysis to identify strengths (e.g., lagoon-centric livelihoods, biodiversity hotspots), weaknesses (e.g., absent wastewater treatment, limited tourist accommodations), opportunities(e.g., Ramsar Convention recognition), and threats (e.g., saltwater intrusion); semi-structured interviews with 45 key stakeholders (30 villagers, 10 local officials, 5 NGO representatives), revealing community priorities and ecological concerns; quantitative datasets on water quality, demographic trends, and livelihood dependency ratios. Findings demonstrate Rogbeh’s unique cultural-ecological landscape as a high-potential ecotourism destination. However, critical barriers—notably institutional fragmentation, sanitation deficiencies, and seasonal eco-nomic instability require systematic intervention. The study advocates a three-pillar solution: eco-sensitive infrastructure: reed-built lodges using solar energy, grey-water recycling, and elevated walkways to minimize wetland disruption; community led governance: tourism coopera-tives allocating 30% of revenues to local healthcare/education, with microgrants for women-led enterprises; this model positions Rogbeh as a replicable prototype where cultural resilience, ecological stewardship, and equitable benefit-shar-ing catalyze holistic sustainability in marginalized wetland communities offering transformative insights for global South contexts facing similar climate-poverty nexuses.